The languange of social media and adolescent mental well-being: A case study of the role of social workers in dealing with cyberbullying - Nur Sandy, Bintang Junior; Pandadi, Fadry Ramadan; Ramadhanti, Nayla Qalisha; Dhita, Adinda Fadillah Leila Farah; Rizkyanfi, Mochamad Whilky; Kardeti, Denti; Ibrahim, Syaeful (JOURNAL OF Mental Health Concerns, 2025)
Background: The development of social media has significantly changed the communication patterns of adolescents. The language used in digital interactions not only serves as a means of communication but can also affect the emotional state and mental well-being of adolescents. Purpose: To analyze the impact of language use on social media on adolescent mental health and to examine the role of social workers in handling cyberbullying cases. Method: Literature study by collecting data from various sources such as books, scientific journals, and academic articles. Results: The use of negative language such as ridicule, insults, and hate speech can cause stress, depression, and even lower self-confidence in adolescents. Conversely, the use of positive and empathetic language contributes to the creation of a healthy digital environment. Social workers have a strategic role in providing digital literacy education, conducting psychosocial assistance, and building collaborative networks between schools, families, and communities to prevent and handle cyberbullying. Conclusion: A holistic approach that emphasizes language ethics in the virtual world is needed as part of efforts to improve the mental well-being of adolescents in the digital age. Keywords: Adolescent Mental Well-Being; Cyberbullying; Social Worker Intervention.